Between empowerment and self-discipline: Governing patients' conduct through technological self-care. (September 2018) - Petrakaki, Dimitra; Hilberg, Eva; Waring, Justin
Abstract: Recent health policy renders patients increasingly responsible for managing their health via digital technology such as health apps and online patient platforms. This paper discusses underlying tensions between empowerment and self-discipline embodied in discourses of technological self-care. It presents findings from documentary analysis and interviews with key players in the English digital health context including policy makers, health designers and patient organisations. We show how discourses ascribe to patients an enterprising identity, which is inculcated with economic interests and engenders self-discipline. However, this reading does not capture all implications of technological self-care. A governmentality lens also shows that technological self-care opens up the potential for a de-centring of medical knowledge and its subsequent communalization. The paper contributes to Foucauldian healthcare scholarship by showing how technology could engender agential actions that operate at the margins of an enterprising discourse. Highlights: Digital health policy in UK assumes an enterprising & empowered patient identity. Tensions between empowerment & discipline occur as patients self-care digitally. Digital health creates space for agential actions that improve communal health. A health-making agency operates in the margins of governmental self-care discourse.